Hormonal-immunologic status and peculiarities of nourishment in obese subjects - I. A. Troshina; I. M. Petrov; T. A. Gagina; I. V. Medvedeva; V. V. Maleyev (Бюллетень сибирской медицины, 2007)
Nourishment peculiarities of 120 patients aged from 41 years having excess body mass and obesity were investigated. Interre-lations with changed hormonal-immune status were assessed. Method of food taking rate developed in the Institute of Nourishment, RAMS, taking into account nourishing peculiarities of Russian population was used. Study results revealed, that patients had imbal-ance concerning main macro- and micronutrients: nourishment regimen was disturbed in 90% of cases, taking main part of energy value was shifted to the second half of a day, increased calorie content of nourishment, excess of monosaccharides in the setting of decreased physical activity were seen which plays the main role in the development and advancing obesity, increased level of leuco-cytes, of TNF-α, IFN-γ, humoral immunity link imbalance, increased serum concentration of leptin and insulin which is closely cor-relates with excess body mass and nourishment peculiarities.